Emphasizing one leg facilitates single-leg training using standard cycling equipment - Staples, T. J.; Do-Duc, A.-A.; Link, J. E.; Martin, J. C. (Scandinavian Journal of Medicine & Science in Sports, 2020)
Purpose: Single-leg cycling exercise is one of the most potent, but underutilized, stimuli for promoting peripheral muscle respiratory capacity. Special ergometers used to facilitate single-leg cycling, while maintaining biomechanics similar to double-leg cycling, are not widely available. This lack of availability of specialized ergometers may explain why single-leg cycling has not been widely implemented as standard clinical practice. Therefore, we explored the extent to which participants could emphasize one leg and de-emphasize the other to perform "single-leg emphasis cycling" using standard cycle ergometers. Methods: Sixteen athletic participants performed single-leg emphasis cycling, emphasizing each leg in separate trials, and double-leg cycling. Pedal forces and limb kinematics were collected and used to calculate joint-specific work and power at the ankle, knee, and hip. Results: Study participants were able to produce approximately three times as much power with their emphasized leg compared to the de-emphasized leg during single-leg emphasis cycling. Ankle plantar flexion, dorsiflexion, knee extension, and hip extension work produced during single-leg emphasis cycling did not differ from those during double-leg cycling (all P > 0.60). Hip and knee flexion work during single-leg emphasis cycling exhibited small but significant differences (both P < 0.05) from double-leg cycling. Conclusions: These results demonstrate that single-leg emphasis cycling provides a convenient alternative to single-leg cycling requiring specialized ergometers, therefore facilitating improved training in clinical and athletic populations using commonly available equipment. Further, biomechanics during single-leg emphasis cycling closely approximated double-leg cycling ensuring that training adaptations are highly applicable to double-leg cycling.